The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41467-023-41345-z
|View full text |Cite
|
Sign up to set email alerts
|

A R-loop sensing pathway mediates the relocation of transcribed genes to nuclear pore complexes

Arianna Penzo,
Marion Dubarry,
Clémentine Brocas
et al.

Abstract: Nuclear pore complexes (NPCs) have increasingly recognized interactions with the genome, as exemplified in yeast, where they bind transcribed or damaged chromatin. By combining genome-wide approaches with live imaging of model loci, we uncover a correlation between NPC association and the accumulation of R-loops, which are genotoxic structures formed through hybridization of nascent RNAs with their DNA templates. Manipulating hybrid formation demonstrates that R-loop accumulation per se, rather than transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…While studies have shown associations between R-loop formation and changes in chromatin accessibility, histone modifica-tions, and nuclear organization (P. B. Chen et al, 2015;Penzo et al, 2023;Sanz et al, 2016), the causal relationships and mechanistic links remain mostly elusive. Integrative approaches combining chromatin conformation capture techniques with R-loop mapping methods can elucidate how R-loops influence chromatin architecture and gene expression regulation, providing insights into their functional consequences in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown associations between R-loop formation and changes in chromatin accessibility, histone modifica-tions, and nuclear organization (P. B. Chen et al, 2015;Penzo et al, 2023;Sanz et al, 2016), the causal relationships and mechanistic links remain mostly elusive. Integrative approaches combining chromatin conformation capture techniques with R-loop mapping methods can elucidate how R-loops influence chromatin architecture and gene expression regulation, providing insights into their functional consequences in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2023). There is relatively little published work that has directly addressed the question of how selective tethering of RNA to chromatin can be achieved: For S. cerevisiae mutants of the TREX complex, chromatin retention has been convincingly linked to the formation of R-loops (Penzo et al, 2023). In that case, retention coincides with downregulation of the CPAC component Fip1, a co-factor of the poly(A) polymerase, and defects in polyadenylation (Saguez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This process can also induce torsional stress that interferes with fork progression, and indeed, some of the TREX-2 components are targeted by the DNA damage checkpoints to alleviate such an effect ( Bermejo et al 2011 ). However, a recent study proposes that, when formed, R-loops promote the relocation of genes to the nuclear pore in a process that is mediated by RPA and sumoylation to prevent genetic instability ( Penzo et al 2023 ). We still need to define how the nuclear localization (whether in the nucleoplasm or the nuclear periphery) impacts the origin and fate of R-loops.…”
Section: Rna Biogenesis Processing and Export Factors As Barriers To ...mentioning
confidence: 99%